PERAN PESERTA DIDIK DALAM MELESTARIKAN TARIAN BELO MESUSUN BUDAYA LOKAL ACEH TENGGARA DI SMP NEGERI 3 BADAR - Rezeki Daifatun Hasanah; Ponidi Ponidi; Silvia Tabah Hati (Al-Ikram : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to analyze the role of students in preserving the belo mesusun dance as a form of local culture in Southeast Aceh, especially in SMP Negeri 3 Badar. This study uses a qualitative research type using a case study method. The data obtained using data collection techniques in the form of observation, interviews, and documentation. The purpose of this study was to determine the implementation, values, strategies, and roles of students in preserving the belo mesusun dance at SMP Negeri 3 Badar. The results of this study indicate that (1) the implementation of the belo mesusun dance at SMP Negeri 3 Badar has become a routine activity that is carried out every year, especially during the commemoration of Teacher's Day and the farewell event for class IX. (2) the belo mesusun dance is a cultural heritage that is rich in social values, such as friendship, harmony, togetherness, unity and mutual cooperation. (3) SMP Negeri 3 Badar has several effective strategies to preserve the belo mesusun dance. They make the dance an extracurricular activity so that students can learn and practice regularly and students also often appear at various events, both inside and outside the school. (4) students at SMP Negeri 3 Badar play an important role in preserving the belo mesusun dance, which is part of the local culture of Southeast Aceh. They routinely practice and perform at various school events, such as the farewell event for grade IX students and commemorating teacher's day, and then they invite their friends and family to get to know the culture. The results of this study can be an example for other schools to encourage the role of students in preserving the belo mesusun dance as part of an effort to cultivate local cultural values ​​in the school environment.